TEACHING ENGLISH AS A SECOND LANGUAGE (ESL) - Akhmedova Fatima Turayevna (Journals Park Publishing, 2024)
This article about teaching English as a Second language. It has given many advices, approaches, and some learning platforms which are useful for teachers who work as foreign languages teacher. Moreover, it includes some information about assessments for ESL. There is exist some barriers in learning languages.
Keywords: ESL, cultural aspects, learning apps, interactive websites, multimedia resources, online communication platforms, discussion, assessment.